Tipping the balance between erythroid cell differentiation and induction of anemia in response to the inflammatory pathology associated with chronic trypanosome infections - Nguyen, Hang Thi Thu; Radwanska, Magdalena; Magez, Stefan (Frontiers in Immunology, 2022)
Infection caused by extracellular single-celled trypanosomes triggers a lethal chronic wasting disease in livestock and game animals. Through screening of 10 Trypanosoma evansi field isolates, exhibiting different levels of virulence in mice, the current study identifies an experimental disease model in which infection can last well over 100 days, mimicking the major features of chronic animal trypanosomosis. In this model, despite the well-controlled parasitemia, infection is hallmarked by severe trypanosomosis-associated pathology. An in-depth scRNA-seq analysis of the latter revealed the complexity of the spleen macrophage activation status, highlighting the crucial role of tissue resident macrophages (TRMs) in regulating splenic extramedullary erythropoiesis. These new data show that in the field of experimental trypanosomosis, macrophage activation profiles have so far been oversimplified into a bi-polar paradigm (M1 vs M2). Interestingly, TRMs exert a double-sided effect on erythroid cells. On one hand, these cells express an erythrophagocytosis associated signature. On another hand, TRMs show high levels of Vcam1 expression, known to support their interaction with hematopoietic stem and progenitor cells (HSPCs). During chronic infection, the latter exhibit upregulated expression of Klf1, E2f8, and Gfi1b genes, involved in erythroid differentiation and extramedullary erythropoiesis. This process gives rise to differentiation of stem cells to BFU-e/CFU-e, Pro E, and Baso E subpopulations. However, infection truncates progressing differentiation at the orthochromatic erythrocytes level, as demonstrated by scRNAseq and flow cytometry. As such, these cells are unable to pass to the reticulocyte stage, resulting in reduced number of mature circulating RBCs and the occurrence of chronic anemia. The physiological consequence of these events is the prolonged poor delivery of oxygen to various tissues, triggering lactic acid acidosis and the catabolic breakdown of muscle tissue, reminiscent of the wasting syndrome that is characteristic for the lethal stage of animal trypanosomosis.